The impact of multistrain probiotics (Leuconostoc mesenteroides, Lactococcus lactis) on African catfish (Clarias gariepinus) gut microbiota, immunological response, and growth performance - Paritova, Assel; Ussenbayev, Altay; Abdessan, Rauan; Assauova, Zhenisgul Seitkaliyevna; Kuzembekova, Gulnur Berikovna; Omarbekova, Gulzhan; Karabassova, Aiken Sansyzbaevna; Kassen, Aigul Jenisbekkyzy; Kenzhebekova, Zhuldyzay; Abulgazimova, Gulmira Alibayevna; Saingaliyeva, Aruzhan (Frontiers in Immunology, 2025)
IntroductionAquaculture is globally recognized as an effective means of supporting economic growth and livelihood security. However, the sector continues to fall short of projected production targets due to the use of low-quality inputs and inadequate culture techniques. The use of probiotics in aquaculture has been proposed as a nutritional strategy to enhance fish growth and immune responses. This study investigated the effects of dietary supplementation with a multistrain probiotic combination—Leuconostoc mesenteroides and Lactococcus lactis—on growth performance, immune parameters, and gut microbiota in African catfish (Clarias gariepinus).MethodsFish were fed either a basal diet or an experimental diet containing L. mesenteroides a 95 nd L. lactis at 106 CFU/g for 8 weeks.Results and discussionThe probiotic-supplemented group showed significant improvements in feed utilization, alternative complement pathway activity, lactic acid bacterial populations, mucus secretion, and peroxidase activity compared with the control group (p < 0.05). Serum lysozyme activity was also significantly higher in the probiotic-fed group. Furthermore, fish receiving the supplemented diet exhibited superior growth metrics, including weight gain, final body weight, and specific growth rate (p < 0.05). Enhanced superoxide dismutase activity was also observed in the probiotic group. These results suggest that dietary inclusion of L. mesenteroides and L. lactis may serve as an effective immunostimulant feed additive for African catfish aquaculture.